Green one‐pot preparation of α‐Fe2O3@carboxyl‐functionalized yeast composite with high adsorption and catalysis properties for removal of methylene blue. (20th December 2017) - Wang, Ying; Zhang, Wei; Qin, Mian; Zhao, Maojun; Zhang, Yunsong
Abstract : Herein, the α‐Fe2 O3 @carboxyl‐functionalized yeast composite (α‐F@CFYC) was synthesized by direct oxidation of yeast with K2 FeO4 and used as a novel adsorbent/heterogeneous Fenton catalyst for removal of methylene blue (MB). The obtained α‐F@CFYC was fully characterized by scanning electron microscopy, EDX, X‐ray diffraction analysis, Fourier‐transform infrared, thermogravimetry, and X‐ray photoelectron spectroscopy, respectively, and the corresponding results showed that α‐Fe2 O3 nanoparticles were successfully obtained and deposited on yeast surface, as well as more functional groups were introduced/exposed on yeast surface. Furthermore, various influence parameters (eg, contact time, initial pH, and MB concentration) on the adsorption/catalysis ability of α‐F@CFYC for MB have been investigated in detail under ambient conditions. As a result, owing to the synergetic effect of the loaded α‐Fe2 O3 and the introduced/exposed functional groups on yeast surface, the as‐obtained α‐F@CFYC exhibited high adsorption capacities and good catalysis degradation properties for MB.